Encouraging moral development in children - Jones, Chris; Learning Zonexpress (Owatonna, MN : Learning Zonexpress, 2006)
Enter into a dynamic discussion on moral development as hosted by a group of teens who give their opinions on moral situations they have faced. Between the group's discussion times, an expert highlights moral development as it progresses in children. A definition of morality, reasons for the decisions we make, and a look at the behavior of real children in a child care center are all covered in this fast-paced, informative video
Title from title screen
Executive producer, Melanie Nelson
Narrator, Susan Spongberg
Grade 7 to adult
Keywords: Moral development; Moral education; Children -- Conduct of life